Non-anemic Iron Deficiency from Birth to Weaning Does Not Impair Growth or Memory in Piglets - Antonides, Alexandra; van Laarhoven, Serana; van der Staay, Franz J.; Nordquist, Rebecca E. (Frontiers in Behavioral Neuroscience, 2016)
Early iron deficiency is associated with impaired (cognitive) development, the severity of which depends on the timing and duration of the under-supply of iron. To design effective treatment and prevention strategies for iron deficiency in humans, suited animal models are needed. In an earlier study (Antonides et al., 2015) we separated 10 pairs of piglets from their mothers within a few days after birth and reared one sibling with artificial iron-deficient (ID) and the other with balanced control milk until weaning. ID piglets grew slower and showed poorer reference memory performance than their controls in a spatial holeboard task, even weeks after iron repletion. One putative intervening factor in that study was pre-weaning maternal deprivation. In an attempt to refine the piglet iron-deficiency model, we assessed whether piglets reared by sows, but withheld iron supplementation, can serve as animal model of iron deficiency. As sow milk is inherently iron-deficient, piglets normally receive a prophylactic iron injection. Ten pairs of piglets were housed with foster sows until weaning (4 weeks). One sibling per pair was randomly assigned to the control group (receiving iron dextran injections: 40 mg iron per kg body mass on days 3 and 10), the other to the ID group. From weaning, all pigs were fed a balanced commercial diet. Blood samples were taken in week 1, 3.5, 6 and 12. Pre-weaning blood iron values of ID piglets were lower than those of controls, but recovered to normal values after weaning. Hemoglobin of ID piglets did not reach anemic values. Hematocrit and hemoglobin of ID animals did not decrease, and serum iron even increased pre-weaning, suggesting that the piglets had access to an external source of iron, e.g. spilled feed or feces of the foster sows. Growth, and spatial memory, assessed in the holeboard from 10 to 16 weeks of age, was unaffected in ID pigs. We conclude that sow-raised piglets are not a suitable model for iron-deficiency induced cognitive deficits in humans. Based on our previous and the present study, we conclude that growth and memory are only impaired in piglets that suffered from pre-weaning anemia.